138 Is Reddit a Reliable Source for Information on Erectile Dysfunction Treatment?. Issue 1 (1st April 2022) - Jesse, E; Sellke, N; Muncey, W; Callegari, M; Harris, D; Kim, T; Ghayda, RA; Loeb, A; Thirumavalavan, N
ABSTRACT: Introduction: Men commonly turn to the internet for information prior to seeing a physician about erectile dysfunction (ED)[1]. Reddit is a popular and influential social media platform consisting of over 52 million users engaged in discussions regarding a vast array of topics[2]. Reddit can serve as a source of information for urologic conditions[3], but social media has been shown to contain unreliable information when it comes to erectile dysfunction[4]. References: 1. Ferguson, Tom, and Gilles Frydman. "The first generation of e-patients." (2004): 1148-1149. 2. Reddit by the Numbers." Reddit, www.redditinc.com/press . 3. Du, Chris, et al. "I leaked, then I Reddit: experiences and insight shared on urinary incontinence by Reddit users." International urogynecology journal 31.2 (2020): 243-248. 4. Fode, Mikkel, et al. "Quality of information in YouTube videos on erectile dysfunction." Sexual Medicine 8.3 (2020): 408-413. Objective: We sought to identify and characterize the types of ED therapies being discussed by users of the highly influential Reddit website. Methods: Two sub-reddit pages, "Ask Men" and "erectile dysfunction", were chosen for analysis. Posts within the erectile dysfunction sub-reddit were sorted by most popular over all time, and the top 50 threads discussing ED management with at least 2 comments were chosen for analysis. Within the Ask Men sub-reddit, the posts were filtered to include the words "erectile dysfunction". Of these threads, 35 were found to contain discussions relevant to ED treatment, and were thus selected for analysis. Each thread was evaluated for any recommendations for an ED therapy made by the users within the comments, and each therapy was evaluated for congruence with the American Urologic Associated (AUA) guidelines statements for the treatment of ED. Results: The "erectile dysfunction" and "Ask Men" sub-reddit forums consist of 8, 100 and 2.7 million members, respectively. A total of 57 different ED therapies were recommended within the 85 posts that were analyzed. Recommendations for changing sexual habits were the most common (29.8%), followed by seeking assistance from a medical professional or use of medications (21.2%), lifestyle changes (17.0%), and exercise practices (13.4%) (Figure 1). Less commonly recommended therapies included the use of supplements (10.7%), herbal remedies (3.9%), and dietary changes (3.9%). Specific therapies that were recommended most often included counseling from a physician, lowering anxiety or stress reduction, reducing porn, reducing masturbation, and discussing ED openly with a partner. Of the 57 specific treatments that were discussed, only 14 (24.6%) were in line with current AUA guidelines for the treatment of ED (Table 1). Conclusions: ED treatments are commonly discussed on Reddit, with a wide range of therapies being self-reportedly successful among users. Most of the treatments discussed are not supported by strong clinical evidence. An understanding of commonly discussed treatments is valuable for the physician, as this may represent an opportunity to educate the population and guide patient counseling. Disclosure: No